Biocomposites from polyamide 11 reinforced by organic silane modified jute fibers: Fabrication and characterization. Issue 11 (18th October 2021) - Van Cong, Do; Giang, Nguyen Vu; Trung, Tran Huu; Hoang, Thai; Lam, Tran Dai; Tham, Do Quang; Huong, Nguyen Thi
Abstract: Using plant derived polymers for the composite production has been considering as an efficiently attempt to reduce the impacts from the environmental pollution as well as utilizes the benefits they can bring. Fully jute/polyamide 11 (PA11) biocomposites are green materials expected to own many outstanding advantages of both components for example, high‐mechanical performances and especially environmentally friendliness. However, to the best of our knowledge, these materials has not been studied so far. This work focuses on the further modification of alkaline pre‐treated jute fibers by using vinyltrimethoxysilane (VTMS) and evaluates the effect of silanization on the interaction and adhesion between jute fibers and PA11 resin as well as the characteristics of resulting composites. By using Fourier transform infrared, thermogravimetry, mechanical property analysis, color difference measurement, and scanning electron microscopy observations, the contribution of VTMS modification to the enhancement on the interfacial interaction and adhesion between fibers and PA11 resin proved clearly. The results showed that tensile strength, impact strength; and Young's modulus of silanized jute biocomposites increased by 44.1; 26.5 and 55.6%, respectively in comparison to those of untreated fiber biocomposites. Similarly, thermal stability, resistance to water absorption and weathering resistance of obtained biocomposites were improved. Abstract :